Application of Multidisciplinary Rehabilitation Nursing in Patients with Brucellar Spondylitis and Its Effects on Pain, Inflammation, and Immune Function - Zhang Y; Zuo X; Yang X; Li R; Wang H; Yu J; Yang X (Journal of Multidisciplinary Healthcare, 2025)
Ying Zhang,1 Xianhong Zuo,2 Xiao Yang,1 Rui Li,1 Huan Wang,1 Jiantao Yu,1 Xinming Yang1 1Department of Orthopedics, The First Affiliated Hospital of Hebei North University, Zhangjiakou, Hebei Province, 075000, People’s Republic of China; 2School of Nursing, Zhangjiakou University, Zhangjiakou, Hebei, 075000, People’s Republic of ChinaCorrespondence: Xinming Yang, Email yzx569@126.comObjective: This study evaluated the effects of multidisciplinary rehabilitation nursing on postoperative outcomes in patients with brucellar spondylitis, focusing on pain, inflammation, immune function, emotional state, sleep quality, spinal mobility, adverse reactions, and patient satisfaction.Methods: A retrospective analysis was conducted on 87 patients who underwent surgery for brucellar spondylitis between January 2020 and June 2024. Patients were divided into two groups: the Routine Group (n=43, receiving standard nursing care) and the Combined Group (n=44, receiving additional multidisciplinary rehabilitation nursing). Outcomes were assessed using the Visual Analog Scale (VAS), inflammatory markers (CRP, ESR, WBC), immune indicators (CD4+, CD8+, CD4+/CD8+), emotional scales (SAS, SDS), sleep quality (PSQI), spinal function (ODI), incidence of adverse reactions, and satisfaction (NSNS).Results: The combined group exhibited significantly greater improvements than the routine group across most parameters. Postoperative pain (VAS) decreased more markedly at days 1 and 7. Inflammatory markers (CRP, ESR, WBC) and immune function (increased CD4+, CD4+/CD8+ and decreased CD8+) improved significantly by postoperative day 7, particularly in the combined group. Psychological status (SAS, SDS), sleep quality (PSQI), and spinal mobility (ODI) also improved more in the combined group. Adverse reaction rates were comparable between groups. However, patient satisfaction was significantly higher in the combined group (89.13%) than in the routine group (71.74%).Conclusion: Multidisciplinary rehabilitation nursing, when integrated with conventional care, significantly improves pain control, inflammatory response, immune function, emotional well-being, sleep quality, and spinal mobility in patients with brucellar spondylitis, without increasing adverse events, and results in higher patient satisfaction.Keywords: brucellar spondylitis, multidisciplinary rehabilitation nursing, effectiveness, pain, inflammation, immune function